Diabetes in pregnancy and risk of near-miss, maternal mortality and foetal outcomes in the USA: a retrospective cross-sectional analysis. (19th April 2021) - Tavera, Gabriella; Dongarwar, Deepa; Salemi, Jason L; Akindela, Oyinkansola; Osazuwa, Itohan; Akpan, Eyerusalem B; Okolie, Ugonna; Johnson, Marilynn; Spooner, Kiara K; Akpan, Ubong I; Yusuf, Korede K; Chukwudum, Chidinma; et al.
ABSTRACT: Background: The prevalence of diabetes in pregnant women has increased in the USA over recent decades. The primary aim of this study was to assess the association between diabetes in pregnancy and maternal near-miss incident, maternal mortality and selected adverse foetal outcomes. Methods: We conducted a retrospective, cross-sectional analysis among pregnancy-related hospitalizations in USA between 2002 and 2014. We examined the association between DM and GDM as exposures and maternal in-hospital mortality, maternal cardiac arrest, early onset of delivery, poor foetal growth and stillbirth as the outcome variables. Results: Among the 57.3 million pregnant women in the study population, the prevalence of GDM and DM was 5.4 and 1.3%, respectively. We found that pregnant women with DM were three times more likely to experience cardiac arrest (OR = 3.21; 95% CI = 2.57–4.01) and in-hospital maternal death (OR = 3.05; 95% CI = 2.45–3.79), as compared to those without DM. Among pregnant women with GDM and DM, the risk for early onset of delivery was higher, compared to women without GDM or DM. Conclusion: A diagnosis of diabetes prior to pregnancy contributes significantly to the risk of maternal cardiac arrest, maternal mortality and adverse foetal outcomes.